Voice pedagogy: Empowering rural learners through podcast-based cultural exchange and digital equity in the digital era - Ramli, Santiana (Journal of Islamic, Social, Economics and Development, 2025)
In today’s Digital Era, equitable access to English proficiency and digital literacy remains a pressing challenge for students in rural Malaysian schools. This study introduces the VOICE Pedagogy (Voicing Our Identity through Culture and Exchange), a low-cost, podcast-based learning framework designed to enhance ESL speaking skills through experiential learning and intercultural storytelling. Grounded in Sociocultural and Experiential Learning theories, the model guides learners through four structured phases Voice (topic selection), Open (digital production), Interact (peer feedback), and Connect (reflection) to build CEFR-aligned speaking competence while strengthening cultural identity. A quasi-experimental pre-test and post-test design was implemented over eight weeks with 30 rural primary students at A1 proficiency level. Data from speaking assessments, questionnaires, and podcast artefacts revealed statistically significant improvement in speaking performance (d = 2.17), alongside high post-intervention mean scores for Technological Self-Efficacy (M = 4.15) and Intercultural Awareness (M = 4.55). Qualitative analysis further indicated greater confidence in communication and deeper appreciation of cultural heritage. The findings validate the VOICE Pedagogy as an innovative, sustainable, and scalable model for bridging linguistic and digital divides. By empowering students to become confident digital communicators and cultural mediators, the framework offers a transformative pathway toward equitable, future-ready education in the Digital Era.